Inability to work in chosen mental illnesses - Warchoł-Sławińska, Ewa; Książek, Piotr; Furtak, Marzena; Włoch, Krzysztof; Drop, Bartłomiej; Drop, Katarzyna (Polish Journal of Public Health, 2011)
The current diagnostic-decisive situation confirms the growing number of people who are treated because of their mental illnesses and disorders. The number of people who are treated because of their affective disorders, neurosis dysfunctions, dysfunctions caused by stress or somatic disorders has increased. Mental disorders have been placed on the third position amongst medical causes of inability to work for years. An important role in the correct medical diagnosis-making is played by the interview with the examined person and with the people from the person’s environment, as well as the documents from the course of hospital and outpatient treatment and the medical examination. Before applying to receive the pension allowance, the insured who is treated because of mental disorders should use the 182-days allowance period during which the treating psychiatrist ought to analyse the future prognosis concerning the further work ability and use the possibility of sending the patient to therapeutic rehabilitation within the framework of pension prevention. A medical expert or a medical commission depending on the level of organism disability of the insured who is applying to receive the pension allowance, can decide about the plain or partial inability to work or inability to exist independently. In the case of a prognosis which presents the possibility of the patient’s returning to work within the 12 months following the finished allowance period, they can determine the entitlement to receive the rehabilitation allowance.